2007
DOI: 10.1002/eji.200636429
|View full text |Cite
|
Sign up to set email alerts
|

Identification and hormonal regulation of a novel form of NKp30 in human endometrial epithelium

Abstract: This study reports the discovery and steroid hormonal regulation of a novel glycosylated form of NKp30 in human endometrial epithelium. NKp30 is a member of the immunoglobulin superfamily and one of three existing natural cytotoxicity-triggering receptors. NKp30 is a glycosylated protein and is thought to be selectively expressed in resting and activated natural killer cells. The aims of the present study were to fully characterize NKp30 mRNA and protein in human endometrium during the menstrual cycle, and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…In this context, we and others could show alterations in ligand binding of NKp30 from different (53). Along this line, it has already been shown that depending on the NKp30 isoform distinct signals are transmitted (48).…”
Section: Stalk-ig Variantsupporting
confidence: 65%
“…In this context, we and others could show alterations in ligand binding of NKp30 from different (53). Along this line, it has already been shown that depending on the NKp30 isoform distinct signals are transmitted (48).…”
Section: Stalk-ig Variantsupporting
confidence: 65%
“…The NKP30 gene which, like the NKP44 gene, is located in the class III region of the human MHC encodes a 30 kDa protein that is expressed on all mature NK cells 10 . In addition, NKp30 can be expressed on cord blood T cells after IL‐15 exposure, 32 on Vδ1 + T cells in presence of IL‐2 and IL‐15 upon TCR engagement, 33 as well as on endometrial epithelial cells after progesterone stimulation 34 . The NKp30 molecule is composed of one extracellular immunoglobulin domain.…”
Section: Ncrsmentioning
confidence: 99%
“…The intracellular tail of NKp30 has no signaling motif but its transmembrane domain associates via a charged amino acid with immunoreceptor tyrosine-based activation motif (ITAM)-bearing adapters (CD3f and FcRc). NKp30 is mostly restricted to NK cells although recent studies have shown protein expression on umbilical cord blood T cells after IL-15 stimulation and on endometrial epithelial cells following progesterone exposure [17,18]. Moreover, the recently identified IL-22-producing mucosal innate lymphoid cell population that shares properties with LTi (lymphoid tissue inducer) and NK cells also expresses NKp30 [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast NKp30c promotes IL-10 secretion, relaying an immunosuppressive signal through a rapid phosphorylation of p38 MAP kinase (see after for the reference). An additional layer of regulation could be provided by the existence of several glycosylation profiles of NKp30 [17]. At present, these important issues have to be unveiled.…”
Section: Introductionmentioning
confidence: 99%